Last Post for the Gold Coast: Heart of a Nation and the Japanese ‘Colonisation’ of Queensland in the late 1980s - Morris, Narrelle (Taylor & Francis, 2004)
The rise of ‘Japan-bashing’ in the 1980s is frequently characterised as a disappointing, discordant or disastrous shift in relations between the West and Japan. Despite its faults, ‘Japan-bashing’ dispelled the considerable air of ambivalence that had been held concerning Japan in the post-war period. For many in the United States, Canada, Europe, Asia and Australia, ambivalence towards Japan and the Japanese was replaced with apprehension on the one hand and some degree of anger on the other, as the successful trajectory of the Japanese economy during the ‘bubble’ era of the 1980s appeared to set Japan against the West in the competition for control of the future. Issues of unequal and allegedly unfair trade with Japan, for example, attracted and maintained the attention of scholars, business leaders, politicians and the media alike. Some commentators spoke of the renewed need to ‘contain’ Japan , employing World War II and Cold War metaphors to represent Japan as a danger to the West. In this atmosphere, Japanese investment in the West became a contentious question in many parts of the world, as for many Westerners such investment seemed very similar to an economic invasion . In Australia, for example, Japanese investment evoked the age-old fears of invasion from the north by the ‘yellow peril’ and the memories of Japan’s militarism against Australia in World War II. In addition, the question of Japanese investment found its own niche in Australia’s historically deep-seated uneasiness about Asia’s geographical proximity. It helped to fuel the already controversial debate about the ‘Asianisation’ of Australia, the process of the nation’s shift away from Europe towards ‘Asia’, which was argued to be having a considerable, and perhaps detrimental, impact on the national-cultural identity of the nation. Finally, Japanese investment became one more catalyst of the wider debate about globalisation, particularly how the integration of Australia into a universal ‘global’ can and does impact on the particularist diversity of the ‘local’.